PERAN ZAT GIZI MAKRO TERHADAP KEJADIAN DEMENSIA PADA LANSIA - Idral Purnakarya (Jurnal Kesehatan Masyarakat Andalas, 2009)
From 2000 to 2004, deathsfrom dementia increased by 32. 8 percent. One of risk factors dementia was diet (macronutrient intakes). Several studies have shown significantly that a higher intake of carbohydrate and protein not only to improve the general health but also to improve cognitive function and memories. Elderly intake the most total fat and saturated fat had the highest risk of dementia.